(3eYGde GdOjf aj edGP GdeLJgOjfs - (3GdTGej GdYGedj, CHh efUhQ, GHf GdTgjO GdKGfj, GHf GdTgjO GdKGfj, GdMSf Hf Rjf GdOjf Hf Ydj GdTGej GdYGedj, J (B1011(3g` (B1602(3es ((3eMeO LYaQ Hf MSf GdLjdGfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdeJYGdj aj YR LdGdg Yf eWGQM GdCagGe (B... (3hGdebUO GdChd aj HjGf aVjdI GdYde hPcQ fHP eeG jLH Ydi GdYdeGA eQGYGJg hHjGf RjGOI TQa Yde Gdabgs
(3BNQgG (B:s
(3BNQgG(B: (3adCf GdGaJGA HeG jMJed GdJChjd hEf cGf eMJedG EdG Cf GMJeGd GdJbjI Ydi XGgQ GdeYdhe ef CMhGd GdCFeI CbQH hCXgQ aPGdc cGa aj GdJQLjM acdGe GdTjN QMeg Gddg JYGdi YfOj gh GdMbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 192s
(3GdPQjYI, L (B21: 130s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs